Peningkatan PHBS melalui Penyuluhan Cuci Tangan Pakai Sabun (CTPS) pada Pekerja Pabrik Makanan Ringan Kahiji Snack Kota Tasikmalaya - Wulan Sundari; Anuy Nurofiat; Adis Anindya Rahmadhani; Rini Handriani; Nening Siti Khoeriah; Nazwa Rahmadina G; Alia Dwi Andini; Nadia Febriana (STIKES Columbia Asia Medan, 2025)
Handwashing with soap is a fundamental sanitation practice proven effective in preventing the spread of various infectious diseases. In the workplace, particularly in the food industry, the implementation of handwashing with soap is essential to protect workers’ health and ensure product quality and safety. Observations at the Kahiji Snack factory in Tasikmalaya City indicated that the practice of handwashing with soap remains relatively low. To address this issue, counseling sessions and the installation of educational posters were conducted to enhance workers’ knowledge and awareness of clean and healthy behavior in the workplace. The methods used included an initial survey, interviews, educational sessions, and the distribution of posters and hand soap. The Wilcoxon test results showed a significant improvement in workers' knowledge, with an average post-test score of 9.86 compared to the pre-test score of 6.57 (p = 0.041).